Penerapan Akupresure untuk Mengurangi Nyeri Haid pada Remaja Putri - Eva Tresanita Damanik; Yekti Murbarani; Florida; Noviyanti; Syalmah; Melgita Sari Nurjayanti Saputri; Ari Widyaningsih (Universitas Ngudi Waluyo, 2025)
Dysmenorrhea is pain that occurs during menstruation and can be very disruptive to daily activities. Menstrual pain is a common complaint experienced by many women and is a symptom, Adolescence is a problem of transition from puberty to adulthood or the process of growing towards mental, emotional, social and physical maturity. During adolescence, physical changes occur accompanied by changes in the reproductive organs. Dysmenorrhea in some adolescents is a torture in itself that must be experienced every month. In general, the treatment of dysmenorrhea pain is divided into two categories, namely pharmacological and non-pharmacological. One of the midwifery care that can be given to reduce menstrual pain or dysmenorrhea is acupressure. Acupressure is a massage or pressure on the meridian points of the body. The problem of menstrual pain or dysmenorrhea still occurs in many adolescent girls at the Tanjung Palas but there is no treatment to overcome it. In fact, menstrual pain or dysmenorrhea can affect the daily activities of adolescent girls including difficulty concentrating, emotional conflict, tension, anxiety, and disrupting the learning process, feeling uncomfortable, decreased activity in the learning process. Based on the problems that arise, community service activities are needed to overcome this. The activity began with an opening and pre-test, secondly the delivery of material about Acupressure to reduce menstrual pain in adolescent girls as well as the practice of doing acupressure to reduce menstrual pain, thirdly the closing and post-test which was attended by 16 adolescent girls. From these activities, it was found that there was an increase in the knowledge of adolescent girls about acupressure to reduce menstrual pain in adolescent girls. Abstrak Dismenore adalah rasa nyeri yang terjadi saat menstruasi dan bisa sangat mengganggu aktivitas sehari-hari. Nyeri haid ini merupakan keluhan umum yang dialami oleh banyak perempuan dan merupakan gejala, Masa remaja merupakan masalah peralihan dari pubertas ke dewasa atau proses tumbuh kearah kematangan mental, emosional,sosial dan fisik. Pada masa remaja terjadi perubahan fisik yang disertai dengan perubahan organ reproduksi. Dismenore pada sebagian kaum remaja merupakan siksaan tersendiri yang harus dialami setiap bulannya. Secara umum penanganan nyeri dismenore terbagi dalam dua kategori yaitu farmakologis dan non farmakologis. Salah satu asuhan kebidanan yang dapat diberikan untuk mengurangi nyeri haid atau dismenore adalah akupresure. Akupresure adalah pemijatan atau penekanan pada titik-titik meridian tubuh. Permasalahan nyeri haid atau dismenore ini masih banyak terjadi pada remaja putri di Tanjung Palas namun belum ada penanganan untuk mengatasinya. Padahal, nyeri haid atau dismenore dapat mempengaruhi aktivitas sehari-hari remaja putri diantaranya sulit berkonsentrasi, konflik emosional, ketegangan, kecemasan, dan mengganggu proses belajar, merasa kurang nyaman, penurunan keaktifan dalam proses pembelajaran. Berdasarkan masalah yang muncul, maka diperlukanlah kegiatan pengabdian masyarakat untuk mengatasi hal tersebut. Kegiatan diawali dengan pembukaaan dan pree test , kedua penyampaian materi tentang Akupresure untuk mengurangi nyeri haid pada remaja putri sekaligus praktik melakukan akupresure untuk mengurangi nyeri haid, ketiga penutup dan post tes yang di hadiri oleh 16 remaja putri. Dari kegiatan tersebut didapatkan ada peningkatan pengetahuan remaja putri tentang akupresure untuk mengurangi nyeri haid pada remaja putri.